Automatic Geographic Information System algorithm for temporal mangrove observation: A case study in Gopek Beach, North Banten - Della Ayu Lestari; Willdan Aprizal Arifin; Novi Sofia Fitriasari; Taufiq Ejaz Ahmad; Amien Rais; Dhea Rahma Azhari (Universitas Negeri Malang, 2022)
Temporal observation is a series of processes started by collecting the necessary data, which is then processed, so that valid information is obtained to support the right decision. To increase the ease of data collection, an automatic algorithm is needed to increase efficiency, shorten the time, and reduce the required resources. The automatic algorithm based on the geographic information system developed in this study was applied to monitoring mangrove forests in Gopek Beach, located on the north coast of Serang, Banten. Using the cloud computing process from an automatic algorithm, the results of vegetation monitoring showed increased efficiency in time and resources. Thus, this study can be used for Geographic Information Systems learning materials in schools or universities.